Effect of β2‐adrenergic receptor polymorphisms on epinephrine and exercise‐stimulated lipolysis in humans. Issue 5 (20th May 2014) - Du, Shichun; Joyner, Michael J.; Curry, Timothy B.; Eisenach, John H.; Johnson, Christopher P.; Schrage, William G.; Jensen, Michael D.
Abstract The β2‐adrenergic system is an important regulator of human adipose tissue lipolysis. Polymorphisms that result in amino acid substitutions in the β2‐adrenergic receptor have been reported to alter lipolysis. We hypothesized that variations in the amino acid at position 16 of the β2‐adrenergic receptor would result in different lipolytic responses to intravenous epinephrine and exercise. 17 volunteers homozygous for glycine at position 16 (Gly/Gly, nine female) and 16 volunteers homozygous for arginine at position 16 (Arg/Arg, eight female) of the β2‐adrenergic receptor participated in this study. On one study day participants received infusions of epinephrine at submaximal (5 ng kg−1 min−1) and maximal (40 ng kg−1 min−1) lipolytic doses. The other study day volunteers bicycled for 90 min at 50–60% of maximum oxygen consumption (VO2max). [9, 10‐3H] Palmitate was infused both days to measure free fatty acid – palmitate kinetics. Oxygen consumption was measured using indirect calorimetry. Palmitate release rates in response to epinephrine and exercise were not different in the Gly/Gly and Arg/Arg participants. The only statistically significant difference we observed was a lesser ΔVO2 in Arg/Arg volunteers in response to the submaximal epinephrine infusion. The polymorphisms resulting in Arg/Arg and Gly/Gly at position 16 of the β2‐adrenergic receptor do not result in clinically meaningful differences in lipolysis responses to epinephrine or submaximal exercise.